Drug Repurposing for Duchenne Muscular Dystrophy: The Monoamine Oxidase B Inhibitor Safinamide Ameliorates the Pathological Phenotype in mdx Mice and in Myogenic Cultures From DMD Patients - Vitiello, Libero; Marabita, Manuela; Sorato, Elisa; Nogara, Leonardo; Forestan, Giada; Mouly, Vincent; Salviati, Leonardo; Acosta, Manuel; Blaauw, Bert; Canton, Marcella (Frontiers in Physiology, 2018)
Oxidative stress and mitochondrial dysfunction play a crucial role in the pathophysiology of muscular dystrophies. We previously reported that the mitochondrial enzyme monoamine oxidase (MAO) is a relevant source of reactive oxygen species (ROS) not only in murine models of muscular dystrophy, in which it directly contributes to contractile impairment, but also in muscle cells from Collagen VI-deficient patients. Here we now assessed the efficacy of a novel MAO-B inhibitor, safinamide, using in vivo and in vitro models of Duchenne muscular dystrophy (DMD). Specifically, we found that administration of safinamide in 3-month old mdx mice reduced myofiber damage and oxidative stress, and improved muscle functionality. In vitro studies with myogenic cultures from mdx mice and DMD patients showed that even cultured dystrophic myoblasts were more susceptible to oxidative stress than matching cells from healthy donors. Indeed, upon exposure to the MAO substrate tyramine or to hydrogen peroxide, DMD muscle cells displayed a rise in ROS levels and a consequent mitochondrial depolarization. Remarkably, both phenotypes normalized when cultures were treated with safinamide. Given that safinamide is already in clinical use for neurological disorders, our findings could pave the way towards a promising translation into clinical trials for DMD patients as a classic case of drug repurposing.